2014
DOI: 10.1371/journal.pone.0105013
|View full text |Cite
|
Sign up to set email alerts
|

Refined Candidate Region for F4ab/ac Enterotoxigenic Escherichia coli Susceptibility Situated Proximal to MUC13 in Pigs

Abstract: F4 enterotoxigenic Escherichia coli (F4 ETEC) are an important cause of diarrhea in neonatal and newly-weaned pigs. Based on the predicted differential O-glycosylation patterns of the 2 MUC13 variants (MUC13A and MUC13B) in F4ac ETEC susceptible and F4ac ETEC resistant pigs, the MUC13 gene was recently proposed as the causal gene for F4ac ETEC susceptibility. Because the absence of MUC13 on Western blot from brush border membrane vesicles of F4ab/acR+ pigs and the absence of F4ac attachment to immunoprecipitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 37 publications
2
33
0
1
Order By: Relevance
“…Transmembrane MUC13 prevents ETEC adhesion in pigs [77] and a MUC13 isoform lacking the glycosylated extracellular domain is associated with an increased susceptibility to ETEC [78]. However, some evidence has been published to suggest that, rather than MUC13, it is a neighboring gene region that is involved in the reported ETEC susceptibility [79]. In a 3D villi model with Caco-2 cells, MUC17 reduces infection with Salmonella typhimurium and MUC17 knockdown disrupts tight junction formation and leads to increased Salmonella invasion [80].…”
Section: Barrier Function Mucosal Maintenance and Interactions Withmentioning
confidence: 99%
“…Transmembrane MUC13 prevents ETEC adhesion in pigs [77] and a MUC13 isoform lacking the glycosylated extracellular domain is associated with an increased susceptibility to ETEC [78]. However, some evidence has been published to suggest that, rather than MUC13, it is a neighboring gene region that is involved in the reported ETEC susceptibility [79]. In a 3D villi model with Caco-2 cells, MUC17 reduces infection with Salmonella typhimurium and MUC17 knockdown disrupts tight junction formation and leads to increased Salmonella invasion [80].…”
Section: Barrier Function Mucosal Maintenance and Interactions Withmentioning
confidence: 99%
“…In differing studies, transcription of either MUC13 or MUC20, another gene associate to F4ac binding (176), did not relate to the adhesive phenotype (177). Moreover, biochemical studies were unable to detect an interaction between MUC13 and F4ac and genotyping assays suggested that a yet uncharacterized M13-adjacent orphan gene participates in glycosylation of the F4ac receptor (178). In another investigation, the SNPs or transcription of 12 genes involved in the assembly of glycosphingolipid carbohydrates could not be associated to a F4 binding phenotype (179).…”
Section: Adhesins and Host Receptorsmentioning
confidence: 99%
“…In the study by Goetstouwers et al . (), MUC13 antibodies did not recognize the F4‐specific high molecular weight (MW) glycoproteins under any conditions. Furthermore, the immunoprecipitated MUC13 was not recognized by the F4ac fimbriae.…”
Section: Discussionmentioning
confidence: 93%
“…; Goetstouwers et al . ). Recently, MUC13 was suggested as the causal gene for F4ac susceptibility (Ren et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation